The ubiquitous computing and its importance for the construction of the internet of things and big data - Torres Vargas, Georgina Araceli; Arias Durá, Raquel (Revista General de Información y Documentación, 2014)
It starts from the idea of ubiquitous computing Mark Weiser, the extent to raise the achievement of proposals such as the internet of things and big data depend on the bases given by Weiser. Showing what are the characteristics of the Big data and the Internet of things. The main objective of the paper is to analyze what progress is required to achieve these two technological concepts and information management.